Efeito da dieta de frangos suplementada com folhas de oliveira (olea europaea l.) no desenvolvimento animal e qualidade da carne - Marangoni, Cristiane (2015)
Chickens Cobb received diet supplemented with olive leaves (FO) of the variety Ascolano in amounts of 5 to 10 g/kg diet during the 42 days of growth and was conducted evaluation of animal performance indicating lower mortality rates and better feed conversion animals treated with FO than those who received conventional diet. The adult chickens were slaughtered in a refrigerator and thighs and drumsticks, were stored under refrigeration (4 °C - for 12 days) and freezing (-18 °C - 120 days) sealed in polyethylene containers without vacuum extraction, for monitoring microbiological, oxidative, chemical physical and sensory through descriptive Quantitative Analysis (QDA) and purchase intent (CI). The FO showed no effect on the protein parameters, fat, ash, color and protein oxidation of the flesh, but influenced the values of humidity parameters, pH, aw, liquid exudation by meat and some amino acids compared to control. The amount of 5g/kg FO showed lowering effect of conjugated dienes, TBARs, peroxide value, and had no effect on growth reduction of Staphylococcus aureus, psychrotrophic and mesophilic aerobes, while the use of 10g/kg FO reduced amount of monounsaturated and saturated fatty acids increased the concentration of polyunsaturated fatty acids and inhibited the growth of Enterococcus spp., lactic acid bacteria, coliforms, Pseudomonas, Clostridium perfringens and Escherichia coli in relation to the treatment which received standard diet. Sensory analysis indicated that the ADQ thighs and drumsticks of chickens that received FO had lower perceptions of taste and odor of rancid attributes and best texture characteristics regarding the treatment that received conventional diet. The IC analysis indicated preference thighs and drumsticks chickens fed FO, prevailing as a criterion of choice for improving taste. The meat of the thigh and drumstick lyophilized was used in feeding Wistar male rats for 25 days at the rate of 20% over conventional diet to evaluate the biochemical profile of animal blood. Rats exposed to broilers fed FO did not indicate clinical and hematological toxicity for animals who received conventional diet.